100 Years of Calcium Hydroxide in Dentistry: A Review of Literature - Sahithi Reddy1 , Venkatachalam Prakash2 , Arunajatesan Subbiya3 , Suresh Mitthra4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Ever since the introduction of calcium hydroxide in 1920, it has been widely used in dentistry. This is dueto the therapeutic properties of calcium hydroxide imparted by its high pH and dissociation to form ionsCa+2 and OH?. This makes it a remineralizing agent, a bactericidal or bacteriostatic agent based on the pHconcentration and also an anti-inflammatory agent. It is being applied for various purposes in dentistry likeintracanal medicament, pulp capping agent, root canal sealer, cavity liner, apexification, pulpotomy, canalswith exudate, perforation management and root resorption. This review article aims to describe in detail thevarious properties of calcium hydroxide and applications marking 100 years of its use in dentistry.